2012
DOI: 10.1159/000341457
|View full text |Cite
|
Sign up to set email alerts
|

Furanodiene, a Natural Product, Inhibits Breast Cancer Growth Bothin vitroandin vivo

Abstract: Purpose: Previous studies have reported that the Curcuma wenyujin Y.H. Chen et C. Ling extract, which has a high furanodiene content, showed anti-cancer effects in breast cancer cells in vitro. The present study was designed to evaluate the in vitro and in vivo anti-cancer activity of furanodiene. Methods: The in vitro effects of furanodiene were examined on two human breast cancer cell lines, MCF-7 and MDA-MB-231 cells. Assays of proliferation, LDH release, mitochondrial membrane potential (△Ψm), cell cycle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Many natural compounds and their derivatives have been successfully categorized according to the standard collection of several cancer drugs, such as paclitaxel, vinblastine, and vincristine (Zhong et al, 2012). Newman et al (2003) reported that more than 50% of the novel compounds approved between 1982 and 2002 were derived directly or indirectly from natural compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Many natural compounds and their derivatives have been successfully categorized according to the standard collection of several cancer drugs, such as paclitaxel, vinblastine, and vincristine (Zhong et al, 2012). Newman et al (2003) reported that more than 50% of the novel compounds approved between 1982 and 2002 were derived directly or indirectly from natural compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Curcuma is a commonly prescribed Chinese herb with anticancer potentials. Curcuma extracts and active ingredients have been identified as its main bioactive components with anticancer effect both in vitro and in vivo [12, 13]. Furanodiene significantly inhibited cancer cell proliferation while germacrone and curdione showed no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Isofuranodiene and atractylon are also known for their pharmacological properties. In particular, isofuranodiene shows anticancer and antiangiogenic activity (15)(16)(17)(18)(19)(20)(21)(22), as well as analgesic properties when acting on brain opioid receptors (23). Atractylon exhibits antiinflammatory activity (24), cytotoxicity against various human cancer cell lines (25,26), acaricidal activity (27), and inhibition of Na + , K + -ATPase activity (28).…”
mentioning
confidence: 99%